9+3(x-2)=9-4(x-9)

Simple and best practice solution for 9+3(x-2)=9-4(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3(x-2)=9-4(x-9) equation:


Simplifying
9 + 3(x + -2) = 9 + -4(x + -9)

Reorder the terms:
9 + 3(-2 + x) = 9 + -4(x + -9)
9 + (-2 * 3 + x * 3) = 9 + -4(x + -9)
9 + (-6 + 3x) = 9 + -4(x + -9)

Combine like terms: 9 + -6 = 3
3 + 3x = 9 + -4(x + -9)

Reorder the terms:
3 + 3x = 9 + -4(-9 + x)
3 + 3x = 9 + (-9 * -4 + x * -4)
3 + 3x = 9 + (36 + -4x)

Combine like terms: 9 + 36 = 45
3 + 3x = 45 + -4x

Solving
3 + 3x = 45 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
3 + 3x + 4x = 45 + -4x + 4x

Combine like terms: 3x + 4x = 7x
3 + 7x = 45 + -4x + 4x

Combine like terms: -4x + 4x = 0
3 + 7x = 45 + 0
3 + 7x = 45

Add '-3' to each side of the equation.
3 + -3 + 7x = 45 + -3

Combine like terms: 3 + -3 = 0
0 + 7x = 45 + -3
7x = 45 + -3

Combine like terms: 45 + -3 = 42
7x = 42

Divide each side by '7'.
x = 6

Simplifying
x = 6

See similar equations:

| 1.4q-6.1q+1.4=-26.8 | | 2(x+2)+x=2(x+1)+1 | | 1.4q-6.1+1.4=-26.8 | | 9+2cosx=10 | | r=Ct+a | | m^2-7.5=92.5 | | 7/5y=26/15 | | ((x-3)/6)=2-x | | 3+7x^2+10=0 | | 7/5z-38/45=53/45 | | x-3/6=2-x | | 52/51/91/34 | | -16x^2+14x+13.5=5 | | -(1/2)=x^-2 | | (X-9)(x^2+5x+6)=0 | | 52/51/91:34 | | -16x+14x+13.5=5 | | 1000=16t^2+1900 | | X+50.3x-10= | | (6x+1)(2x+10)=180 | | 3(b-7)-2=3 | | (2x+10)+(6x+1)=180 | | 3f(-3)+h(5)= | | 9+-5x=4 | | -19+x=-19 | | -7(k-8)-(-8k+6)=-2 | | 20z-5-12x=10z+8 | | 1.5/6=3/x | | 0.85(x)=200 | | -7(k-8)-(-k+6)=-2 | | N*1/5=9 | | 10(2+x)=15(x+1)+15 |

Equations solver categories